LABORATORY MODELS OF GROWING FLANGES, AND A COMPARISON WITH OTHER GROWTH MECHANISMS OF BLACK SMOKER CHIMNEYS - Turner J.S. (My University, 1995)
The first measurements of the structure of black smoker chimneys suggested that they form initially by the precipitation of anhydrite from seawater, because of the reverse solubility effect due to the heating of its surroundings by the effluent, rather than directly from the less dense hot plume. This initial growth is followed by replacement of the solid anhydrite framework, successively by iron, zinc and copper sulfides. More recent observations of very large chimneys have shown that later precipitation directly from the plume can occur through the growth of flanges, or large horizontal protrusions at the side of the chimneys. Light sulfide-rich fluid, leaking out of holes in the chimney wall, ponds under these flanges, which grow as the hot fluid percolates through the porous top or flows over their nearly horizontal edges and precipitates as it cools. Both of these processes have been demonstrated in laboratory models using the crystallization of solutes such as KNO3 and Na2CO3 which have a strong dependence of solubility on temperature.Crystallization from the surroundings can be produced using an inflowing plume of cold K2CO3 into a warm nearly saturated KNO3 solution, and in this case an axisymmetric chimney grows in length at a nearly constant rate, and at the same time thickens as further crystallization takes place. Further experiments, in which the inflowing K2CO3 was constrained to spread horizontally near the source, produced a cluster of chimney structures. The first experiments demonstrating the second mechanism, the process of crystallization directly from the incoming fluid, were reported in the context of replenished magma chambers. When dense saturated KNO3 is injected slowly into cold surroundings, some of the incoming fluid is quenched while the rest is forced upwards to form columns with a flat top. These grow upwards as the gravitationally constrained fluid flows over the lip, cooling and crystallizing as it does so. In the new laboratory experiments reported here the same physical effects are observed in a more appropriate ''flange'' geometry if a small deflector plate is provided to produce an initial horizontal flow of the nearly saturated KNO3 solution. Growing flanges have also been produced on the outer face of an existing crystal column, in a geometry which is directly applicable to black smoker chimneys.